Does self-esteem mediate the relationship between loneliness and depression among Malaysian teenagers? - Uba, Ikechukwu (Universiti Putra Malaysia Press, 2012)
The current study examined the mediating role of self-esteem in the relationship between loneliness and depression among teenagers. The participants of the study were 242 teenagers (119 males and 123 females) aged 13 to16 years, from selected secondary schools in the central zone (Selangor) of Malaysia (mean age = 14.67 years; SD = 1.27). Teenage depression was measured using Children Depression Inventory, while loneliness was measured using the Revised UCLA Loneliness Scale, and self esteem was measured using the Rosenberg Self-Esteem Scale. The study discovered that self-esteem had negative and medium correlation with loneliness (r = -.380, p <.01) and depression (r = -.497, p <.01). The study further found a positive and medium correlation between loneliness and depression (r = .493, p <.01). Self-esteem was found to be both the unique predictor of depression and a partial mediator of the relationship between loneliness and depression. Thus, the findings of the study filled the gap in the existing literature on the relationship between loneliness and depression. Recommendations of the study centre on the need for counsellors and psychologists to educate parents on the need to aid the development of self-esteem among their teens.